2010
DOI: 10.1590/s0104-56872010000300006
|View full text |Cite
|
Sign up to set email alerts
|

Competência lexical e metafonológica em pré-escolares com transtorno fonológico

Abstract: TEMA: competência lexical e metafonológica em pré-escolares com transtorno fonológico OBJETIVO: investigar, em um grupo de pré-escolares a influência do transtorno fonológico sobre as competências lexical e metafonológica e a existência de correlações entre ambas. MÉTODO: a amostra foi composta por 56 pré-escolares, 32 meninos e 24 meninas, entre 4:0 a 6:11 anos, que constituíram dois grupo: o Grupo Pesquisa, composto por 28 pré-escolares com transtorno fonológico e o grupo de comparação, composto por 28 pré-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 16 publications
4
18
0
Order By: Relevance
“…Some studies (19,23,26) also considered the use of phonological awareness tests together with the application of multivariate statistical analyses to control the influence of phonological awareness on the results, since this could be positively influencing reading performance (28,29) and, consequently, masking performance in the morphological awareness skill. Another skill controlled (21,23) by means of the Wechsler Intelligence Scale for Children -WISC III (30) was cognitive development.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (19,23,26) also considered the use of phonological awareness tests together with the application of multivariate statistical analyses to control the influence of phonological awareness on the results, since this could be positively influencing reading performance (28,29) and, consequently, masking performance in the morphological awareness skill. Another skill controlled (21,23) by means of the Wechsler Intelligence Scale for Children -WISC III (30) was cognitive development.…”
Section: Resultsmentioning
confidence: 99%
“…The girls performed better in language strategies than boys according to a study described in the literature 16 . Moreover, a study of preschoolers 17 , revealed that gender is not a factor influenced on phonological tasks. In contrast, age influences on phonological tasks and the higher the age the better the performance in these tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigated the abilities and disorders of language in children, who stutter, indicated that this group compared with those who do not stutter, had presented lower scores on several indices of receptive and expressive language [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Methodsmentioning
confidence: 99%
“…The acquisition of phonological awareness enables the development of oral language, communication, reading and writing 26 . A deficit in the mental organization and representation of speech sounds leads to alterations in the processes of perception, analysis and conscious manipulation of syllables 27 .…”
Section: Literature Reviewmentioning
confidence: 99%